Exploring Art and Islamic Elements of Sunan Kalijaga's Da’wa in Web-based Education - Banindro, Baskoro Suryo; Mutmainah, Baridah Mutmainah; Auliya, Nahij Auliya (Nadwa: Jurnal Pendidikan Islam, 2023)
This research aims to develop digital-based educational media highlighting Sunan Kalijaga's role as a saint and artist in Java. This study is important to discuss Sunan Kalijaga’s role in da’wa; first, Sunan Kalijaga employed a unique and effective method of da’wa or proselytizing through art, adapting to the local community's culture. Secondly, the teachings and artistic legacy of Sunan Kalijaga are still preserved and well-maintained in some parts of Western, Central, and Eastern Java. There is a shortage of studies exploring Sunan Kalijaga's role as an Islamic saint and artist through new media like a website. Data were collected by reviewing printed and digital literature, interviews, and field observations. This research adopts a descriptive approach with a literature review method and 5W1H analysis (what, who, why, when, how). This website was chosen as a platform to enable users to interact with the content, thereby increasing interest and understanding of Sunan Kalijaga's role in da’wa. Through the Likert scale usability test, this study concluded that the website design could be used as an educational media for teaching and public use.